식사가 불량한 영유아의 기질과 식행동, 부모의 식행동과 식사지도 방법의 특성 - 김윤정(Yoon Jung Kim); 한영신(Young Shin Han); 정상진(Sang Jin Chung); 이윤나(Yoon Na Lee); 이상일(Sang Il Lee); 최혜미(Hay Mie Choi) (Korean journal of community nutrition, 2006)
The purpose of this study was to determine the characteristics of infants' temperaments and eating behaviors, mothers' eating behaviors and feeding practices in poor eating infants. The participants were 80 infants of 12-24 months (27 poor eaters and 53 matched normal controls) from a hospital and a public health center. Mothers were questioned about their eating behaviors and feeding practices, and infants' temperaments, eating behaviors, and nutrient intakes by one day food recall. Subjects were divided by mean nutrient adequacy ratio (MAR, < 0.75; poor eater). Intakes of Ca, P, Fe, Zn, thiamin, riboflavin, niacin, vitamin C, E, folate were below 75% RDA in poor eaters, whereas protein, thiamin, riboflavin, vitamin B$_6$, C, folate exceeded 125% RDA in good eaters. Rhythmicity of infants' temperaments and eating behaviors, restriction of mothers' eating behaviors and feeding practices were significantly lower, whereas activity levels of infants' temperaments were higher than good eaters. In multiple logistic regression model of poor eaters, activity of infants' temperaments (T, OR: 1.19, CI: 1.05 - 1.35) and attention spans of infants' eating behaviors (A, OR: 1.18, CI: 1.03 - 1.35) were significantly positive, whereas rhythmicity of infants' eating behaviors (R, OR: 0.79, CI: 0.61-0.94) was significantly negative [E (the legit) : -6.8644+0.1712$\times$T-0.2337$\times$R+0.1641$\times$A]. Our findings suggest that examination of eating behaviors, feeding practices, and temperaments will help target interventions to improve infants' food intakes, and these variables should be examined at the time of nutrition counseling.